Robust Techniques for Acoustic Feedback Control in Hearing Aids - Tran, Linh Thi Thuc (Curtin University, 2018)
Adaptive feedback cancellation (AFC) is the approach with the best potential to address the acoustic feedback problem. In this thesis, new AFC methods for hearing aids are investigated, they are based on combinations of widely known techniques such as two-microphone, pre-filter, fast-converging adaptive filter and variable step-size. These proposed methods not only are robust against different types of incoming signals and acoustic feedback paths, but also enhance the convergence/tracking rate while retaining low steady-state error.